2014
DOI: 10.1007/s10750-014-2093-0
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem change and establishment of an invasive snail alter gastropod communities in long-lived Lake Malawi

Abstract: Biotic invasions can have far-reaching effects in isolated, eco-insular systems such as the African Great Lakes, certainly in synergy with other anthropogenic stressors that affect ecosystem stability. Interactions between invasive and indigenous taxa across trophic levels often tend to propagate throughout the ecosystem, but also those at the same trophic level may affect biodiversity. Here, we examine faunal interactions between an invasive Asian morph of the cerithioidean gastropod Melanoides tuberculata an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…All snails collected in Florida from our study were nested within clades containing sequences previously recognized as M. tuberculata, and the topology allowed us to identify likely source populations. Both clades included haplotypes from Malaysia that are also implicated in East African invasions [24,59]. This is consistent with Chiu et al [29] who suggested that haplotypes recovered in other studies of invaded regions (Caribbean, Central America, South America, Africa, and Miami, Florida, West Africa) mainly originated from Malaysia.…”
Section: Genetic Diversity and Invasion Patternssupporting
confidence: 82%
“…All snails collected in Florida from our study were nested within clades containing sequences previously recognized as M. tuberculata, and the topology allowed us to identify likely source populations. Both clades included haplotypes from Malaysia that are also implicated in East African invasions [24,59]. This is consistent with Chiu et al [29] who suggested that haplotypes recovered in other studies of invaded regions (Caribbean, Central America, South America, Africa, and Miami, Florida, West Africa) mainly originated from Malaysia.…”
Section: Genetic Diversity and Invasion Patternssupporting
confidence: 82%